Impact of telmisartan in modifying vascular risk - Jean-Philippe Baguet; Olivier Ormezzano; Gilles Barone-Rochette (Dove Medical Press, 2010)
Jean-Philippe Baguet, Olivier Ormezzano, Gilles Barone-RochetteClinique de Cardiologie, Centre Hospitalier Universitaire de Grenoble, Grenoble, FranceAbstract: Telmisartan, a selective angiotensin II type 1 receptor blocker (ARB), has been investigated in many trials, in particular, in order to assess its antihypertensive effect in various situations and its ability to protect organs susceptible to hypertension. In addition to its antihypertensive properties, it has positive metabolic and vascular effects (partly because of its sustained action). Several large-scale trials have focused on the effect of telmisartan on cardiovascular morbidity and mortality, including comparisons of that with an angiotens-inconverting enzyme inhibitor in subjects at high vascular risk. Telmisartan was used in the largest ARB research programme (the Ongoing Telmisartan Alone and in Combination with Ramipril Global Endpoint Trial [ONTARGET] and Telmisartan Randomized Assessment Study in ACE Intolerant Subjects with Cardiovascular Disease [TRANSCEND] trial).Keywords: angiotensin II receptor blocker cardiovascular risk, hypertension, blood pressure, renin–angiotensin–aldosterone system